Seismic performance of square concrete columns reinforced with grade 600 MPa longitudinal and transverse reinforcement steel under high axial load. (August 2021) - Shi, Qingxuan; Ma, Licheng; Wang, Qiuwei; Wang, Bin; Yang, Kun
Abstract: The aim of this paper is to investigate the seismic behavior of square concrete columns reinforced with Grade 600 MPa steel under high axial load and specify the service strength of Grade 600 MPa longitudinal bars. For these purposes, seven high-strength reinforced concrete cantilever columns with high axial compression ratio (0.64) and low aspect ratio (3.3) were constructed and tested under constant axial loading and cyclic lateral loading. A new configuration of transverse reinforcement was proposed and applied in these specimens. The main variables carried out in the current experiment include longitudinal bars ratio, transverse reinforcing strength, and the spacing of transverse bars. The milestone behaviors of these specimens were estimated and interpreted using multiple performance indexes, including failure pattern, hysteresis response, strength capacity, flexural ductility, energy dissipation capacity, strength degradation, and stiffness deterioration. Test results indicated that these specimens can be satisfied with aseismic requirement of Chinese code GB 50011-2010. Based on the strain of longitudinal bars test results, the service strength of Grade 600 MPa longitudinal bars can be specified as 560 MPa in this study. An added design suggestion is proposed with the amount of transverse reinforcement requirement to ensure seismic performance of these columns using the effective confinement index (k e ρsh fyh / fc '). A fiber section analysis program was conducted in XTRACT finite element software. The analysis show that the failure mode of specimens was transformed with a given high axial compression ratio when the confinement effect of core concrete was considered. The method of the China Concrete Code (GB50010-2010) for determining seismic bending moment capacity of RC column was extended on the basic of confined concrete theory. Compared with experimental results, the conservative calculation results were obtained in this manuscript. It could be referenced for engineering seismic design.